PENGARUH PENGGUNAAN METODE BERMAIN KARTU TERHADAP KEMAMPUAN MENGENAL HURUF PADA PAUD NURUL HUDA DESA MONTOK KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Rina Ardiyati; Wahono Wahono; Naili Saâ€™ida (PROCEEDING UMSURABAYA, 2022)
the purpose of this study was to determine the effect of using the card playing method on the ability to recognize letters in early childhood education in nurul huda, montok village, ban district, pamekasan regency, for the 2021/2022 academic year. based on media observations in a number of kindergartens, apart from being taught singing and motor skills, early childhood students also receive education to recognize the letters of the alphabet and numbers. the research method used in this study uses purposive sampling method, which means that the research area is deliberately selected based on certain objectives and considerations. the results obtained in this study are that there is a moderate positive correlation between the use of the card playing method on the ability to recognize letters in early childhood children, nurul huda, montok village, ban district, pamekasan regency for the 2021/2022 academic year. so on the basis of these data it can be said that , "if using the card playing method is good then the results of the ability to recognize letters are also good and if the use of the card playing method is less then the results of the ability to recognize letters are also lacking". thus, it means that there is a conformity of theory which states that the method of playing cards carried out by the teacher will affect the child's ability to recognize letters.Â Keywords: playing method; cards; purposive sampling